(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Nitrogen % in both straw and grain, nitrogen uptake by straw and grain, total nitrogen uptake and physiological nitrogen use efficiency (PNUE) showed significant differences due to variable nutrient levels at maturity in traditional rice varieties. PNUE ranges from 40.58 to 49.88 (kg/kg N). Significantly higher PNUE without addition of nitrogen (Zero N) indicated the ability of utilization of the native nitrogen by traditional varieties. Traditional varieties produced 49.88 kg grain by the utilization of zero nitrogen treatment followed by 45.93 kg grain in cowdung (10 t/ha), while 40.58 kg grain by the application of 80 kg/ha nitrogen. The higher PNUE in zero nitrogen treatment confirmed the ability of producing similar yield level compared to added nitrogen treatment. Bashful chikon, might be important due to higher nitrogen content and Badiruzzman considered due to more straw nitrogen (0.71%). Barud also showed excellence with regards to PNUE and total nitrogen uptake. Leaf chlorophyll profile showed a very consistent level in all the varieties except Laichi. Soil plant analysis development (SPAD) value ranged from 34.06 to 41.69, while leaf nitrogen ranged from 2.99 to 3.49 %. SPAD value recorded over time showed four distinct patterns during 15 to 90 DAT. Key Words: Genotypic variation, rice varieties, SPAD value, nitrogen use efficiency. DOI: 10.3329/bjar.v34i3.3977 Bangladesh J. Agril. Res. 34(3) : 505-515, September 2009